Issues and ethical guidelines pertaining to blogging / Mardhiah Mohamad - Mohamad, Mardhiah (2006)
Blogging has become something of a big thing in the last few years, and some of the biggest and best known weblogs attract the kind of traffic that even big name e-commerce sites would be jealous of Since weblog have gain popularity as a medium this study is significant for many people and aspect to the area of blogging. Firstly, it is importance to maintain a certain level of values amongst the bloggers in order to encourage them to improve their creativity to express the ideas to others. Secondly, the guidelines that will be propose are useable as a guideline for bloggers in the future to decrease issues and problems that accumulate to the unethical way of blogging and blog abuse. The guidelines also based on the Software Engineering Code and the ACM Code (Institute of Electrical Engineers, Inc, and Association for Computing Machinery, Inc 1999). This study use Extended Technology Acceptance Model (TAM 2002) to identify user's attitudes and perception toward blogging and to address the issues and propose guidelines pertaining to blogging. Primary data were collected through questionnaires and about 200 sets of questionnaires were distributed around UiTM main campus which consists of 16 faculties as a whole.